Javanese Language Representation: A Dialogue and Expression ala Kethoprak in the Film Nyumbang - Purwoko Ajie; Sri Kusumo Habsari; Deny Tri Ardianto; Kundharu Saddhono (Bina Nusantara University, 2023)
The research aimed to examine the usage of the Javanese language to represent the discourse of nyumbang (donation) in the film Nyumbang produced by Montase Film Independen Yogyakarta. It focused on analyzing the discourse semantics of the Javanese dialogues, which took the style expression ala Kethoprak. The primary data are the Javanese dialogues in the film Nyumbang. At the same time, the supporting data were taken from journals, books, newspapers, websites, and supporting media (audiovisuals, interview results, and other documentation). Data analysis techniques included reduction, presentation, and verification of conclusions related to the research object. The results indicate the utilization of a strong Javanese accent, mostly found in Kethoprak's performance, to represent the problematic discourse of nyumbang. The actors who are the members of the Sanggar Kethoprak Merbabu Budaya, Magelang, speaking in Javanese with the Mataram accent, highlight the problematization of the ideology behind the discourse of nyumbang. The Mataram accent, which is the language style of Kethoprak, added with the helpless facial expressions of the actors, provides the interpretation of the raising question of the nyumbang tradition, which has been embedded in Javanese culture. Through some word choices that are exaggerated to produce a sense of helplessness, the tradition of nyumbang, formerly developed to help each other, becomes a social burden. Thus, the research finds that the film Nyumbang provides an effort to maintain the Kethoprak tradition without abandoning the characteristics of its traditional performances, which contain criticisms of tradition in modern life.